Regime change in Libya: the legality and legitimacy of the NATO military intervention in Libya in 2011 - Viļuma, Marta Kristiāna (Riga Graduate School of Law, 2021)
The military intervention in Libya in 2011 has raised a lot of questions regarding legitimacy and legality of the intervention that resulted into regime change in a sovereign state. The intervention was based upon a decision by United Nations Security Council known as Resolution 1973 with the central problem of weak legal and legitimate basis. Seemingly, it is in compliance of the existing procedure that allows the authorization of a military action but its appliance and the limitations set are not particularly and clearly defined. The main research question of this thesis is whether the regime change was authorized by the Resolution 1973 and whether the intervention itself was legal and legitimate? During the research process the aim is to find a clear answer with reasonable arguments while identifying the problematic aspects that might difficult the process of finding an answer stated within the legal norms. In result, the research and analysis shows that the vagueness of legal interpretation of international norms justifies regime change although, morally it may seem unjustifiable
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Military intervention; Libya